An Error-Resilient RISC-V Microprocessor With a Fully Integrated DC-DC Voltage Regulator for Near-Threshold Operation in 28-nm CMOS - Wu, Bing-Chen; Chen, Wei-Ting; Liu, Tsung-Te (IEEE journal of solid-state circuits, 2023)
This article presents an energy-efficient microprocessor design that fully integrates an error-resilient RISC-V core and an embedded dc-dc switched-capacitor voltage regulator (SCVR). The proposed design achieves high energy efficiency, high computation performance, and a small system footprint through several innovations. First, in situ error detection and correction (EDAC) flip-flops (FFs) and an error-resilient static random access memory (SRAM) interfacing technique enable error resilience on the microprocessor without any post-silicon calibration requirement. Next, a fully integrated SCVR featuring a multi-rate successive approximation (MRSA) algorithm and a dynamic conduction loss minimization technique is proposed to achieve high conversion efficiency, high-power density, and fast load regulation. A prototype chip that fully integrates the techniques described above was fabricated in the 28-nm standard CMOS technology with an active area of 0.42 mm ^{2} . The measurement results show that the proposed in situ EDAC effectively minimizes the timing margin without any post-silicon calibration to achieve a high-processor performance of 43 MHz with an energy-delay-product (EDP) of 0.57 \text{pJ}·μ s, showing the state-of-the-art performance and energy efficiency in the standard CMOS technology.